Implementasi Model Pembelajaran PAI dalam Meningkatkan Karakter Siswa - Rohman, Ali (Indonesian Proceedings and Annual Conference of Islamic Education (IPACIE), 2023)
The purpose of this study was to analyze the PAI learning model in improving the character of students by using a social interaction model. The social interaction learning model focuses on the actual environmental setting so that students understand the essence of togetherness and diversity in living together in society later. In carrying out life in society, the ability to socialize is needed because we are social beings and cannot be separated from what is called social interaction with the community by being wrapped in religious norms. The research method used is descriptive qualitative. With a qualitative approach, researchers can observe, understand, and analyze accurately and comprehensively related to PAI learning with social interaction learning models to improve the character of students. The findings are as follows: a) The implementation of the social interaction learning model in PAI lessons in the classroom emphasizes problem-solving in small groups which will later illustrate the group results in front of the class, b) The PAI learning model using social interaction is very influential in improving the character of participants education that is realized by better social interaction and prioritizing Islamic norms.